Iron deficiency and neurodevelopment among low birth weight infants: a cross-sectional study in a tertiary center in Tanzania (Tanzania Medical Journal, 2017)
Background: iron deficiency anaemia is known to cause delayed neurodevelopment. Likewise infants born with low birth weight are also prone to neurodevelopment. The impact of both presence of iron deficiency and low birth weight is therefore expected to augment this delayed or impaired neurodevelopment. This relationship has not been elucidated in any appreciable level. We therefore considered studying iron deficiency among low birth weight infants and assessing their neurodevelopment. In children, however its impact is not clearly known among low birth weight infants.Broad objective: To assess neurodevelopment of low birth weight infants and its relation to their iron status and nutritional status.Methods: A cross-sectional study of 270 low birth weight infants was assessed during follow-up at neonatal clinic at Muhimbili National Hospital at 12 weeks postnatal. . They underwent the Bayley Mental Developmental Scoring Tests, serum ferritin and complete blood counts. The BMDS test raw scores were converted into percentiles. Cognitive, language and motor development scores were considered normal with score of ?85 percentile of raw scores and poor with if the score was <85. Iron deficiency were considered if serum ferritin was <12µ/dl. Results: The prevalence of poor scores were 90% in cognitive, 60% in language (60%) and 88% in motor development. The prevalence of iron deficiency was 34.1%. Among those not receiving iron supplementation, Poor cognitive and language scores were associated with iron deficiency, while motor scores were not. Wasting was associated with poor language score.Conclusion. Low birth weight, iron deficient and wasted infants had significant poorer neurodevelopmental outcomes confirming that Iron deficient, low birth weight infants are more prone to poor neurodevelopmental outcomes. Recommendations; Early iron supplementation program should be adhered to and a close follow-up of these vulnerable children be done to ensure that their iron and hemoglobin levels are normal. Further large scale studies on the temporal relationship of iron and neurodevelopment are required.